Kualitas Pelayanan Crystal Lotus Hotel Berdasarkan Review Tamu Di Traveloka Crystal Lotus Hotel Service Quality Based On Guest Reviews In Traveloka - Awaludin, Awaludin; Kuntari, Erlina Daru; Handayani, Lutfi; Arifin, Samsul (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2023)
This study aims to find out how the service quality of Crystal Lotus Hotel Yogyakarta is based on guest reviews on Traveloka. The object of this research is guest reviews based on Traveloka with a sample of 122 reviews which uses the Slovin formula. In preparing this final project, using qualitative research methods with observation and documentation data collection techniques.The results obtained from the research in this writing are based on the service quality of Crystal Lotus Hotel Yogyakarta based on guest reviews at TravelokaTangible Dimensions,the positive reviews about the rooms are comfortable and clean, there are bacon, the breakfast menu is delicious and varied, the hotel is very comfortable, the employees are beautiful and handsome, there is a parking lot, views, a swimming pool for children, complete facilities, strategic location, and close to the center small gifts. Negative guest reviews, namely: some hotel facilities that have problems, room cleanliness and guest comfort.Dimensi Reliability, positive reviews from guests about good and fast service. Negative guest reviews namely: service room service nothing, guests complain about the TV being damaged at the reception but it hasn't been repaired, and the check-in process is long.Responsiveness Dimension, positive reviews of guests on the wishes and needs of guests, always trying to help guests when guests need it. Negative guest reviews namely: long and long-winded service, guest requests that are not delivered, and staff responses that are not convincing for guests.Assurance Dimension, positive reviews about staff friendliness, and courtesy. Negative reviews such as the security staff at the basement are not friendly.Empathy Dimension, Positive reviews from guests about being allowed to check-in prematurely. Know the wishes of guests. Then the negative reviews for guests are: guest requests are not fulfilled by the hotel so that guests review negatively